One-Step and Colorimetric Detection of Fish Freshness Indicator Hypoxanthine Based on the Peroxidase Activity of Xanthine Oxidase Grade I Ammonium Sulfate Suspension - Guo, Chen; You, Shuhan; Li, Changmei; Chen, Tiantian; Wang, Xiudan (Frontiers in Microbiology, 2021)
Global food waste problem especially aquatic products spoilage stimulates the accurate freshness analysis of food products. However, it still remains a great challenge to realize in-field determination of fish freshness at the time of use. In the present study, a colorimetric enzyme biosensor was developed for one-step detection of hypoxanthine (Hx), which is an important intermediate of ATP decomposition during fish storage. We demonstrated that xanthine oxidase Grade I ammonium sulfate suspension (XOD-ASS) possessed peroxidase activity. It could oxidize different peroxidase substrates, including 3,3’,5,5’-tetramethylbenzidine (TMB), 2,2’-azino-bis (3-ethylbenzo-thiazoline-6-sulfonic acid) diammonium salt (ABTS), and o-phenylenediamine (OPD) in the presence of H2O2, producing visible color reactions. Further experiment indicated that XOD-ASS displayed effective peroxidase activity and could be used for H2O2 detection. Based on this, a one-step Hx detection method was established using only XOD-ASS as the catalyst. The method displayed a good linear relationship in the range from 20 μM to 100 μM with a detection limit of 6.93 μM. Additionally, we successfully applied this method in testing Hx accumulation in sea bass fish samples of different storage time. The recovery values are ranged from 97.44 to 102.56%. Excitedly, compared with other methods, our proposed method provides a robust advantage on economical reaction system, facile preparation, short time consumption, and moderate reaction temperature. We believe that this method shows good application prospect for on-site fish freshness determination.